FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN DANA MASYARAKAT PADA BANK PEMERINTAH PROVINSI RIAU (TAHUN 2000-2015) - Ainul Qalbina Nurri; Rosyetti '; Rahmita Budiartiningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to know the great influence of economic growth, saving interest rate and inflation agains the absorption of public funds in government banks of Riau Province. The data used in this research is the data time series from 2000 to 2015, sourced from a representative Bank Indonesia and Badan Pusat Statistik of Riau. Methods of analysis used is multiple linear regression analysis by using SPSS 23 for windows. In this research, the dependent variable is the absorption of public funds while the independent variables are economic growth, saving interest rate and inflation. From the results of this research were obtained that the variable on economic growth, saving interest rates and inflation simultaneously give significant effects against the absorption of public funds with F of 34,474 and significant level of 0,000. From the results of the t-test with significant levels of partial α = 5% is obtained that the variables of economic growth effect positive and significant, saving interest rate effect negative and significant and inflation effect negative and insignificant against the absorption of public funds. While economic growth has variables influence the more dominant against the absorption of public funds in government banks of Riau Province with significant level of 0,001. Great influence posed (Adjusted R-Square) by a third variable to the variable dependent is 87,0%, 13,0% while the rest is affected by other variables not examined in this study.Keywords: Public Funds, Economic Growth, Saving Interest Rate and Inflation